The Influence of Stress on the Severity of Acne Vulgaris in Adolescents - Ulfatul Latifah; Iroma Maulida; Ardhi Henda K (Indonesian Journal of Global Health Research, 2025)
In Indonesia, acne vulgaris is a common skin disease, almost everyone has experienced acne vulgaris, especially in young people, it occurs around 85 - 100%. The highest prevalence occurs in women aged 14-17 years, 83-85%, and men aged 16-17 years. 19 years old, accounting for 95-100%. One of the factors that causes acne to appear is stress. Stress is pressure that occurs due to a mismatch between the desired situation and expectations. Teenagers who experience acne will certainly feel uncomfortable. This study aims to determine the effect of stress on the severity of acne vulgaris in adolescents. Method: Jenis penelitian ini merupakan penelitian analitik kuantitatif dengan pendekatan observasional menggunakan desain cross-sectional. Populasi dalam penelitian ini adalah remaja di Kota Tegal dengan jumlah sampel sebanyak 288 yang diambil secara acak. Uji analisis menggunakan uji Chi-square. Results: This study aims to determine the effect of stress on the severity of acne vulgaris in adolescents. Method: This type of research is quantitative analytical research with an observational approach using a cross-sectional design. The population in this study were teenagers in Tegal City with a total sample of 288 taken randomly. Test the analysis using the Chi-square test. Conclusions: Stress factors influence the severity of acne vulgaris, the more stressed a teenager is, the more severe the incidence of acne vulgaris they suffer.